You are on page 1of 1

# Theorem 6.16.

## Let D be a dense subset of a metric space X, let Y be a complete metric

space, and let f : D → Y be uniformly continuous. Then f has a unique continuous
extension to a function F : X → Y . That is, there is a unique continuous map F : X → Y
s.t. F (x) = f (x) for all x ∈ D.
Proof. Uniqueness is immediate from Proposition 6.10 (in lectures).
Let p ∈ X. As D is dense there is a sequence, {rn }, in D s.t. rn → p. Then {rn } is
Cauchy in X and so by Proposition 6.15, {f (rn )} is a Cauchy sequence in the complete
space Y , and so must converge. Define F (p) = limn→∞ f (rn ). If p ∈ D, then by continuity
of f on D, we have f (rn ) → f (p), and so F (p) = f (p). Therefore F is an extension of f .
We first claim that F (p) does not depend on the choice of {rn }. Let {rn0 } be an
another sequence in D converging to p. As above, we know that f (rn0 ) → L for some
L ∈ Y , and we wish to show that L = F (p). Let  > 0 and (by uniform continuity of f on
D) choose δ > 0 so that if r, r0 ∈ D satisfy dX (r, r0 ) < δ, then dY (f (r), f (r0 )) < . Since
rn and rn0 both converge to p, the triangle inequality easily shows that dX (rn , rn0 ) → 0
and so there is an N so that n > N implies dX (rn , rn0 ) < δ which in turn implies that
dY (f (rn ), f (rn0 )) < . We have therefore proved that

## dY (F (p), L) ≤ dY (F (p), f (rn )) + dY (f (rn ), f (rn0 )) + dY (f (rn0 ), L).

By (1) and the definitions of F (p) and L, the right side of the above approaches 0 as
n → ∞. Therefore the left side of the above must be zero and so F (p) = L, as required.
It remains to show that F : X → Y is continuous. For this, fix p ∈ X and let xn ∈ X
n n
converge to p. By definition F (xn ) = limm→∞ f (rm ), where {rm : m ∈ N } is a sequence
in D converging to xn as m → ∞. By taking m large enough we can find a point rn ∈ D
so that dX (xn , rn ) < 1/n and dY (F (xn ), f (rn )) < 1/n. Again, a simple application of the
triangle inequality (recall that xn → p) shows that rn → p and so f (rn ) → F (p) (by the
above, the definition of F (p) does not depend on the choice of {rn }). Therefore

dY (F (xn ), F (p)) ≤ dY (F (xn ), f (rn )) + dY (f (rn ), F (p)) < 1/n + dY (f (rn ), F (p)) → 0,